2008
DOI: 10.4049/jimmunol.180.3.1854
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Peroxisome Proliferator-Activated Receptor γ (PPARγ) Suppresses Rho GTPases in Human Brain Microvascular Endothelial Cells and Inhibits Adhesion and Transendothelial Migration of HIV-1 Infected Monocytes

Abstract: Under inflammatory conditions (including HIV-1 encephalitis and multiple sclerosis), activated brain endothelium enhances the adhesion and transmigration of monocytes across the blood-brain barrier (BBB). Synthetic ligands that activate the peroxisome proliferator-activated receptors (PPARs) have anti-inflammatory properties, and PPAR stimulation prevents the interaction of leukocytes with cytokine stimulated-endothelium. However, the mechanism underlying these effects of PPAR ligands and their ability to inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
67
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 98 publications
(73 citation statements)
references
References 51 publications
4
67
0
Order By: Relevance
“…34 Our experiments showed that interactions of monocytes with TNF␣-stimulated BMVECs resulted in diminished barrier function (TEER decrease); GSK3␤ inactivation significantly protected the barrier from injury. We have previously shown that engagement of BMVECs by monocytes results in activation of Rho GTPases (like RhoA, Rac) 16 inducing an increase in barrier permeability and phosphorylation of tight junction proteins (occludin, claudin-5); consequently, inhibition of RhoA/Rho kinase prevented these effects. 19 Whether GSK3␤ inhibition prevents tight junction modifications or interferes with GTPase activity that lead to barrier dysfunction remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…34 Our experiments showed that interactions of monocytes with TNF␣-stimulated BMVECs resulted in diminished barrier function (TEER decrease); GSK3␤ inactivation significantly protected the barrier from injury. We have previously shown that engagement of BMVECs by monocytes results in activation of Rho GTPases (like RhoA, Rac) 16 inducing an increase in barrier permeability and phosphorylation of tight junction proteins (occludin, claudin-5); consequently, inhibition of RhoA/Rho kinase prevented these effects. 19 Whether GSK3␤ inhibition prevents tight junction modifications or interferes with GTPase activity that lead to barrier dysfunction remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Michael Bernas and Marlys Witte, University of Arizona, Tucson, AZ) were isolated from microvessels derived from temporal or hippocampal tissue removed during operative treatment of epilepsy as described. 16 Tissue used for BMVEC isolation was outside epileptogenic foci. The procedures were approved by the Temple University Institutional Review Board.…”
Section: Cell Culture and Reagentsmentioning
confidence: 99%
See 2 more Smart Citations
“…35 Furthermore, strategies to prevent activation of two GTPases, Rac1 and RhoA, in the brain microvascular endothelial cells resulted in decreased adhesion and migration of HIV-1-infected monocytes across the brain endothelium. 36 It is plausible that the combined effects of methamphetamine and HIV-1 central nervous system infection could be attributable to activation of transcription factors and GTPases leading to BBB dysfunction secondary to oxidative stress.…”
mentioning
confidence: 99%